Effects of sowing environments and n-levels on dry matter partitioning and phenological stages in wheat varieties of n-w Himalayas, India (Bangladesh Journal of Botany, 2025)
The study was conducted in rabi seasons of 2015-16 and 2016-17 to explore the potential of different wheat varieties under changing climatic scenario which is prevalent during grain filling/reproductive stages. The wheat crop was sown under different sowing environments (early, normal and late) with three nitrogen levels (100, 125 and 150 kg/ha). The variety WH 1105 was found to be the best in all the sowing environments, and early sown conditions were observed best with higher dose of nitrogen (150 kg/ha) under irrigated conditions. There was a positive relationship between total dry matter production at anthesis and grain yield of wheat (R2=85) irrespective of varieties, sowing environments and nitrogen levels.Bangladesh J. Bot. 54(2): 221-231, 2025 (June)